Association between glottis screen location and intubation difficulty: a retrospective video laryngoscopy study - Kai-Yuan Cheng; Pang Hsu Liu; Yung-Cheng Su; Yen-Yu Chen; Ya-Ni Yeh; Jih-Chun Lin; Ming-Jen Tsai (BMC Emergency Medicine)
Abstract Background In emergency settings, difficult intubations often occur unexpectedly despite pre-intubation assessments. Traditional glottic view scoring systems for direct laryngoscope may not apply to video laryngoscopy. With video laryngoscopy, the vertical location of the glottis on the monitor can be clearly defined. If the glottis location is associated with intubation difficulty, it could serve as a simple indicator for anticipating intubation challenges. This study aimed to investigate the relationship between the glottis screen location during video laryngoscopy-guided intubation and the success and timing of the first-attempt intubation. Methods We retrospectively analyzed laryngoscopy recordings from adult intubations in the emergency department of a tertiary teaching hospital in Chiayi, Taiwan, using the C-MAC video laryngoscope between March 2020 and April 2023. The vertical screen location of the vocal cords, determined by the arytenoid cartilage position after laryngeal blade engagement, was categorized into upper and lower locations for analysis. The primary outcome was first-attempt intubation success within 90 s, analyzed using Kaplan-Meier survival curves and multivariable Cox proportional hazard analysis. Results Among 209 laryngoscopy records, 113 had the arytenoid in the lower field of view and 96 in the upper field. Kaplan-Meier analysis showed a significantly lower cumulative success rate for intubations with a higher arytenoid location (log-rank test, P < 0.001). Multivariable Cox models, adjusted for factors like modified Cormack-Lehane grade, blade tip engagement, and other intubation findings, confirmed the arytenoid’s location as an independent predictor of successful intubation within 90 s, with an adjusted hazard ratio of 0.55 (95% confidence interval, 0.38–0.79) for the upper location group compared to the lower (P < 0.001). Conclusions A higher screen location of the vocal cords after blade engagement is associated with reduced first-attempt intubation success. Assessing glottis location during video laryngoscopy intubation provides a quick method to anticipate intubation challenges.